2013
DOI: 10.1101/gad.210377.112
|View full text |Cite
|
Sign up to set email alerts
|

Suv4-20h2 mediates chromatin compaction and is important for cohesin recruitment to heterochromatin

Abstract: Cohesin plays an important role in chromatid cohesion and has additional functions in higher-order chromatin organization and in transcriptional regulation. The binding of cohesin to euchromatic regions is largely mediated by CTCF or the mediator complex. However, it is currently unknown how cohesin is recruited to pericentric heterochromatin in mammalian cells. Here we define the histone methyltransferase Suv4-20h2 as a major structural constituent of heterochromatin that mediates chromatin compaction and coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
162
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(175 citation statements)
references
References 42 publications
12
162
1
Order By: Relevance
“…In addition, because H4K20 methylation is processive and is among the modifications with the slowest rate of formation (Zee et al 2010), it may take longer for SUV4-20H1 to reach full processivity in the absence of basal levels of H4K20me3 and/or H3K9me3. It is noteworthy that Suv4-20 enzymes can be targeted to chromatin through interaction with HP1, which mediates stable SUV4-20H2 binding synergistically (Schotta et al 2004;Hahn et al 2013). Because HP1β appears in the paternal chromatin only after S phase (Santos et al 2005;Santenard et al 2010) and because SUV4-20H1/H2 are known to function mostly in G1 (Zee et al 2010), the lack of HP1 on the paternal pronucleus together with the processivity nature of SUV4-20 enzymes would explain why H4K20me3 is detected in the paternal chromatin only at the two-cell stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because H4K20 methylation is processive and is among the modifications with the slowest rate of formation (Zee et al 2010), it may take longer for SUV4-20H1 to reach full processivity in the absence of basal levels of H4K20me3 and/or H3K9me3. It is noteworthy that Suv4-20 enzymes can be targeted to chromatin through interaction with HP1, which mediates stable SUV4-20H2 binding synergistically (Schotta et al 2004;Hahn et al 2013). Because HP1β appears in the paternal chromatin only after S phase (Santos et al 2005;Santenard et al 2010) and because SUV4-20H1/H2 are known to function mostly in G1 (Zee et al 2010), the lack of HP1 on the paternal pronucleus together with the processivity nature of SUV4-20 enzymes would explain why H4K20me3 is detected in the paternal chromatin only at the two-cell stage.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the longer nature of SUV4-20H1, which has 406 more amino acids than SUV4-20H2, may modulate its processivity. Strong overexpression of Suv4-20h2 in embryonic stem cells leads to increased chromatin compaction around chomocenters and consequent mitotic segregation defects (Hahn et al 2013). However, we did not detect segregation defects in SUV4-20H2-expressing embryos.…”
Section: Discussionmentioning
confidence: 99%
“…However, H3K9me3 signals persist at DAPIdense foci in cells in the absence of SUV4-20H1 and SUV4-20H2. Interestingly the C-terminal domain of SUV4-20H2 can bind to isoforms of HP1, key components of heterochromatin, and through their chromodomains can direct the binders of H3K9me3 (20,(42)(43)(44). This suggests a model in which H3K9me3 recruitment of HP1 brings in SUV4-20H2 to establish an H4K20me3 landscape at heterochromatin.…”
Section: H4k20me3mentioning
confidence: 99%
“…Using this method, Fan et al demonstrated that a loss of linker histone H1 leads to a decrease in nucleosomal spacing (Fan et al 2003). Digestion experiments with increasing concentrations of MNase (Hahn et al 2013) or with increasing incubation times (Gilbert et al 2007) provide diagnostic digestion patterns that have been used to imply changes in chromatin 'compaction'.…”
Section: Nuclease Sensitivitymentioning
confidence: 98%